INTERLIGIOUS DIALOGUE TODAY - Kurshid Alam Khan (Journal of Dharma, 1994)
day, more than ever, man is in need ot religion. The lack of spirituality in our lives and inter-personal relationships explain why society is being dehumanised. This dehumanization of society is to my mind the prime cause for so much of violence and bloodshed that we see all over the world. I see here scholars, theologians and philosophers assembled from all over the world who profess different faiths and beliefs. I am, myself, deeply interested in reliQion and humanism. Therefore, your invitation to me was god-sent.